KEANEKARAGAMAN JENIS BURUNG DIURNAL DALAM KAWASAN CAGAR ALAM MANDOR KABUPATEN LANDAK - Windharti, Yayuk; Nurdjali, Bachrun; anto, Eri (Universitas Tanjungpura, 2013)
Wildlife bird is one of the natural resources that have an important role in the lives of both ecological, recreational, economic, tourism and in terms of education and science, so that its presence is absolutely necessary not only for the present but also for the future. Extinction of a species of bird in the wild means the loss of natural resources are very precious existence therefore need to be preserved. This study aims to determine the diversity of bird species that are diurnal Nature Reserve area mandor regency landak. The study was conducted on the 2nd of February-3 March 2013. Result observations made at three study sites Heath forest, peat swamp forest, mining Logged diurnal found 92 species of birds with details on Heath forest (50 species and 500 individuals), Peat Swamp Forest (86 species with 549 individuals), and the former mining area (48 species with 426 individuals). Highest species diversity in Peat Swamp Forest with morning time value of diversity H = 1.73947, time of day H = 1.74264 and the evening H = 1.73440. The result of the calculation is known that the dominance of the largest diurnal bird habitat Heath forest with morning dominance index C = 0.04314, C = 0.03687 lunch time and evening time C = 0.03789. The similarity index is the highest type in Peat Swamp Forests and Forest Heath with IS = 50.88% while the lowest type on the similarity index Heath forest and mining Logged in value IS = 48.93%. Key Words : Diversity, type, birds, diurnal, nature reserves mandor